Free movement of patients in the EU : a patient's perspective / Gabriella Berki. - Berki, Gabriella (Intersentia, 2018)
The issues of patient mobility have been high on the EU's political agenda for the last two decades. However, the adoption of the Patient Mobility Directive, which had to be implemented by the Member States by 25 October 2013, added to the complexity of an already complex legislative system. Thus both, the new questions raised by the new piece of legislation and the old questions left without satisfactory answers call for new solutions. So particularly at a time, when the national application of the Directive is beginning to have an impact on border-crossing patients it is imperative to revisit patient mobility. However, in contrast to the existing literature, Free Movement of Patients in the EU tests the current legal landscape from the perspective of border-crossing patients. How, in a multi-player arena of patients, healthcare providers, healthcare funds, national governments, Union institutions, etc. with colliding ideologies can the legal situation be improved in a way that better serves patients' interests while respecting the responsibilities of the Member States in this field and with the legal tools currently available? This book is of interest to scholars and practising experts dealing with patient mobility or social security issues as well as stakeholders and decision-makers. Dr Gabriella Berki is an assistant professor at the University of Szeged and guest lecturer at the Sorbonne University (Paris, France) and the University of Rijeka (Croatia). She is also a member of two European expert networks funded by the European Commission, FMSSFE Statistics and FreSsco, both active in the fields of social security coordination and the free movement of workers.